A Case for a Deliberative Link in the Representation Process: From Congruence to Resonance. Issue 4 (1st October 2016) - Liston, Vanessa
Abstract : This paper proposes a deliberative link in the representation cycle. The deliberative link supports the articulation of social discourses; preferences transformation and the expression of citizens' judgemental agency. To outline the case, I begin by examining the limitations of congruence theory as a framework for conceptualising the representative system. I then argue for a deliberative link based on the concept of discursive representation put forward by John Dryzek and Simon Niemeyer. Such a link requires advances beyond 'congruence' for measuring responsiveness. I suggest that future research explore 'resonance' in Dryzek's terms.